“Better do not touch” and other superstitions concerning melanoma: the cross-sectional web-based survey - Gajda, Maksymilian; Kamińska-Winciorek, Grażyna; Wydmański, Jerzy; Tukiendorf, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction :To the authors’ best knowledge, there are no data regarding the prevalence of superstitions concerning melanoma among internet users. Aim: To evaluate the prevalence and identify reasons for superstitions associated with excision of pigmented skin lesions as well as to assess the frequency of this procedure. Material and methods : Readers of the scientific portal were invited to complete a fully anonymous e-questionnaire. After collection of questionnaires (5,154) and eliminating incomplete ones, 4,919 surveys were analysed. Results : A total of 4,104 (83.4%) respondents have been aware that the total surgical excision is the only efficient way of melanoma treatment. This familiarity was related to increased skin cancer awareness but was not linked to regular skin self-examination. Over half of the surveyed agreed that “it is better not to touch naevi”. Moreover, 3,510 (71.3%) individuals believed that naevi located in “harmed places” may turn into melanoma. Conclusions : Superstitions associated with surgical treatment of melanoma are widespread. Conducting educational campaigns is necessary, particularly among young people, whose dangerous tanning behaviours are important risk factors for melanoma occurrence in their later life.